A Rare Case of Stroke Secondary to Iron Deficiency Anemia in a Young Female Patient. (28th February 2017) - Gopalratnam, Kavitha; Woodson, Kevin Andrew; Rangunwala, Jigarkumar; Sena, Kanaga; Gupta, Manisha
Abstract : Ischemic strokes occur when there is a sudden obstruction of an artery supplying blood flow to an area of the brain, leading to a focal neurological deficit. Strokes can be thrombotic or embolic in etiology and are associated with underlying conditions such as hypertension and atherosclerosis. Possible etiologies of strokes include cardioembolic disease, hematologic disorders, connective tissue disorders, and substance abuse or can be cryptogenic. Most stroke cases are seen in patients over 65 years of age. However, about one-fourth of strokes occur in young adults. Iron deficiency anemia (IDA) has been described as a known cause for strokes in children, but very few case reports describe this association in adults. We describe a 20-year-old female who presented with sudden onset left side weakness. Magnetic Resonance Imaging (MRI) of the brain demonstrated ischemic infarctions. Patient was also found to be severely anemic. Patient had a thorough work-up including Magnetic Resonance Angiography (MRA) of the brain, echocardiogram, and an extensive screen for thrombophilia disorders. This, however, did not demonstrate a clear etiology. As it has been suggested that IDA is a potential cause for stroke, it is possible the stroke in this young patient was attributable to severe IDA.